2019
DOI: 10.1161/circulationaha.118.039069
|View full text |Cite
|
Sign up to set email alerts
|

Response by Ho et al to Letter Regarding Article, “Genotype and Lifetime Burden of Disease in Hypertrophic Cardiomyopathy: Insights From the Sarcomeric Human Cardiomyopathy Registry (SHaRe)”

Abstract: The Sarcomeric Human Cardiomyopathy Registry (SHaRe) originates from international centers deeply invested in clinical investigation and state of the art management of hypertrophic cardiomyopathy (HCM). Unlike single center studies with relatively small patient cohorts and limited follow-up, the value of SHaRe lies in amassing the scale and diversity of patient experience needed to address fundamental questions regarding the natural history of this complex disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
373
4
6

Year Published

2019
2019
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 198 publications
(400 citation statements)
references
References 5 publications
17
373
4
6
Order By: Relevance
“…In a recent study, it was reported that young age at diagnosis and the presence of a sarcomere mutation are associated with an adverse clinical outcome. 31…”
Section: Finhcm Outcome Studymentioning
confidence: 99%
“…In a recent study, it was reported that young age at diagnosis and the presence of a sarcomere mutation are associated with an adverse clinical outcome. 31…”
Section: Finhcm Outcome Studymentioning
confidence: 99%
“…We collected four additional sets of independent test data to further assess the CardioBoost performance, using variants reported as pathogenic in ClinVar and HGMD 19 (both databases of aggregated classified variants), a diagnostic laboratory referral series from the Oxford Molecular Genetics Laboratory (OMGL), and a large registry of HCM patients, SHaRe 20 . CardioBoost consistently achieved the highest TPRs: predicting the most pathogenic variants with over 90% certainty ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…First, we directly assessed the strength of the association between the specified disease and rare variants stratified by the different tools. We compared the proportions of rare missense variants in a cohort of 6,327 genetically-characterised patients with HCM, from the SHaRe registry 20 , with 138,632 reference samples from gnomAD v2.0 ( Table 3 ). We calculated the Odds Ratio (OR) of each sarcomere gene for all rare variants observed, and for variants stratified by CardioBoost, M-CAP, and REVEL after excluding variants seen in our training data.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An array of cardiomyopathy genes, and other cardiac genes, harbored VUSs in these subjects, and MYBPC3 was noted as having the highest number of VUSs. MYBPC3 truncations are a common cause of hypertrophic cardiomyopathy (1,33), and the MYBPC3 VUSs were all missense, perhaps suggesting a distinct mode of action. In context of genetic testing for cardiomyopathies, variants of uncertain significance are typically returned and can sometimes be interpreted with further familial testing and segregation analysis (34,35).…”
Section: Variants Of Uncertain Significance and Echocardiographic Finmentioning
confidence: 99%